The complete genome of Propionibacterium freudenreichii CIRM-BIA1, a hardy actinobacterium with food and probiotic applications. - Hélène Falentin (Public Library of Science (PLoS), 2010)
Background Propionibacterium freudenreichii is essential as a ripening culture in Swiss-type cheeses and is also considered for its probiotic use. This species exhibits slow growth, low nutritional requirements, and hardiness in many habitats. It belongs to the taxonomic group of dairy propionibacteria, in contrast to the cutaneous species P. acnes. The genome of the type strain, P. freudenreichii subsp. shermanii CIRM-BIA1 (CIP 103027(T)), was sequenced with an 11-fold coverage. Methodology/principal findings The circular chromosome of 2.7 Mb of the CIRM-BIA1 strain has a GC-content of 67% and contains 22 different insertion sequences (3.5% of the genome in base pairs). Using a proteomic approach, 490 of the 2439 predicted proteins were confirmed. The annotation revealed the genetic basis for the hardiness of P. freudenreichii, as the bacterium possesses a complete enzymatic arsenal for de novo biosynthesis of aminoacids and vitamins (except panthotenate and biotin) as well as sequences involved in metabolism of various carbon sources, immunity against phages, duplicated chaperone genes and, interestingly, genes involved in the management of polyphosphate, glycogen and trehalose storage. The complete biosynthesis pathway for a bifidogenic compound is described, as well as a high number of surface proteins involved in interactions with the host and present in other probiotic bacteria. By comparative genomics, no pathogenicity factors found in P. acnes or in other pathogenic microbial species were identified in P. freudenreichii, which is consistent with the Generally Recognized As Safe and Qualified Presumption of Safety status of P. freudenreichii. Various pathways for formation of cheese flavor compounds were identified: the Wood-Werkman cycle for propionic acid formation, amino acid degradation pathways resulting in the formation of volatile branched chain fatty acids, and esterases involved in the formation of free fatty acids and esters. Conclusions/significance With the exception of its ability to degrade lactose, P. freudenreichii seems poorly adapted to dairy niches. This genome annotation opens up new prospects for the understanding of the P. freudenreichii probiotic activity.